Petrogenesis and geodynamic implications of Early Palaeozoic granitic rocks at the Hongshi Cu deposit in East Tianshan Orogenic Belt, NW China: Constraints from zircon U–Pb geochronology, geochemistry, and Sr–Nd–Hf isotopes. (13th August 2019) - Cheng, Xihui; Yang, Fuquan; Zhang, Rui; Xu, Qiangfen; Yang, Chengdong
Abstract : The Early Palaeozoic granitoid rocks represent a volumetrical component of the eastern part of the Dananhu–Tousuquan island arc belt of the East Tianshan and preserve useful information about the tectonomagmatic history of this region. The Hongshi intrusion primarily consists of granodiorite, which intrudes the Ordovician–Silurian Daliugou Formation in the Kalatag area. Zircon U–Pb dating of magmatic zircons from the granodiorite was formed at 426.6 ± 2.3 Ma, suggesting that the intrusion was emplaced in the Middle Silurian. Geochemically, granodiorite belongs to the metaluminous calc‐alkaline I‐type granitoids associated with a narrow range of SiO2 concentration (63.53–67.71 wt.%), A/CNK values ranging from 1.01 to 1.12. They have high Ba, LREE, and LILE contents and low abundance of HREE and HFSE. These samples displayed MgO contents of 1.38–1.52 wt.%, resulting in low K2 O/Na2 O ratios of 0.11–0.33 and intermediate Mg # values of 29.03–37.31, with high Sr/Y, La/Yb, and Ba/Th ratios, positive εNd(t) (6.60 to 7.95) and εHf(t) (13.1–16.0), low ( 87 Sr/ 86 Sr)i (0.704113–0.704312), and low Nb/U and Ta/U ratios. These features indicated that the parental magma of the granodiorite was probably derived from a juvenile crust with no significant mantle component involvement. Based on the regional geology and geochemical evidence, the Hongshi granodiorite is considered to have formed in an arc setting, associated with the northward subduction of the young Kangguer Ocean slab beneath the Dananhu island arc.